2013
DOI: 10.1177/1948550613486677
|View full text |Cite
|
Sign up to set email alerts
|

Love on the Margins

Abstract: National data on romantic relationships reveal a prominent gap between members of devalued and dominant groups in the United States, with devalued group members experiencing less positive relationship outcomes. However, little research examines how social stigma affects relationship quality for members of devalued groups and moderating factors have generally not been explored in the literature. In the current studies, we experimentally examined the effects of social stigma on relationship quality among women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Stigma has been shown to be an important determinant of population health (Hatzenbuehler, Phelan, & Link, 2013), and deleterious associations with romantic relationship functioning may be one avenue by which psychological and physical health become impaired for sexual minorities (Doyle & Molix, 2014c). In addition, we suspect that these processes are not only unique to sexual minorities but also operate among members of other devalued groups (e.g., racial minorities, women; for example, Doyle & Molix, 2014a, 2014b, 2014c; Lincoln & Chae, 2010; Trail et al, 2012). However, prejudice and discrimination may be especially important sources of stress for sexual minority relationships because negative attitudes and behaviors directed toward sexual minorities often stem from or include reference to their sexual and romantic partners (i.e., members of the same sex).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma has been shown to be an important determinant of population health (Hatzenbuehler, Phelan, & Link, 2013), and deleterious associations with romantic relationship functioning may be one avenue by which psychological and physical health become impaired for sexual minorities (Doyle & Molix, 2014c). In addition, we suspect that these processes are not only unique to sexual minorities but also operate among members of other devalued groups (e.g., racial minorities, women; for example, Doyle & Molix, 2014a, 2014b, 2014c; Lincoln & Chae, 2010; Trail et al, 2012). However, prejudice and discrimination may be especially important sources of stress for sexual minority relationships because negative attitudes and behaviors directed toward sexual minorities often stem from or include reference to their sexual and romantic partners (i.e., members of the same sex).…”
Section: Discussionmentioning
confidence: 99%
“…This may be an effect of age, whereby sexual minorities become more adept at managing stigma as they grow older. However, it is also possible that older participants may have been somewhat more likely to be in more committed or serious relationships, which may buffer some of the deleterious effects of social stigma (Doyle & Molix, 2014b). …”
Section: Discussionmentioning
confidence: 99%
“…Past work has confirmed that the stress of prejudice and discrimination is associated with impaired psychological and physical health (Paradies, 2006; Pascoe & Richman, 2009; Williams & Mohammed, 2009). Because stressors have also been shown to negatively affect social relationships (McCubbin & Patterson, 1983; Randall & Bodenmann, 2009), some scholars have proposed that prejudice and discrimination may lead to impaired social health (e.g., Doyle & Molix, 2014b; Trail, Goff, Bradbury, & Karney, 2012). However, no studies of which we are aware have tested whether self-reported discrimination explains disparities in social health between sexual minorities and heterosexuals.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that relationship length can moderate the relation between social stigma (including gender-based and racial discrimination) and relationship quality (Doyle & Molix, 2014b). Another intervening variable in the interaction between stigma and relationship quality is depressive symptoms (Jaremka, Lindgren, & Kiecolt-Glaser, 2013), because higher stigma levels are linked to poorer relationship quality, in part, due to the presence of the depressive symptoms.…”
Section: De Los Reyes and Gonzálezmentioning
confidence: 99%
“…Although many scholars agree that social stigma negatively affects relationship quality in several ways (Doyle & Molix, 2014b), few studies on HIV stigma have upheld the HIV stigma framework or have posited a bidirectional relation in which relationship quality could also have a positive impact on the experiences or correlates of HIV stigma. Fostering relationship quality among HIV-affected male couples through couple-oriented strategies could prove useful to diminish the individual outcomes of some of the mechanisms of HIV stigma.…”
Section: Future Directions In Researchmentioning
confidence: 99%